Pendampingan Preservasi Koleksi Buku di Perpustakaan Nusa Tunas Unggulan (NTU) Academy Medan - Hilda Syaf'aini Harefa; Maretta Ginting; Ronnie Togar Mulia Sirait (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2023)
Preservation of library materials in the library environment is an activity that should get attention. preservation or maintenance of library materials in general is the activity of preserving, maintaining and repairing library materials from destruction, fragility caused by humans, insects, dust, light and the natural environment. In practice, collection preservation activities are not only the responsibility of librarians. Ideally it also requires awareness of users who utilize and use the collection. The purpose of this activity is to increase understanding regarding book collection preservation and improve skills related to book collection preservation. The result of this activity is that the implementation of community service runs smoothly according to the expectations of the community service implementing team, the participants feel that this community service activity is useful, because the participants are aware of the importance of preserving library materials in preserving library materials owned by the library, Participant responses for the service activities carried out stated that the delivery of the material was good and the participants understood the explanation given. This is shown by the interactive atmosphere between the participants and the service team and by assisting with the preservation of book collections, thus adding insight both theoretically and practically regarding the procedure for repairing damaged book collections and preventing damage to book collections.